Reconstruction using massive allografts after resection of extremity osteosarcomas the study design: A retrospective cohort study. (September 2015) - Han, Gang; Wang, Yan; Bi, Wenzhi; Jia, Jinpeng; Wang, Wei; Xu, Meng; Zheng, Xiaoque; Mei, Lina; Yang, Mingyu
Abstract: Purpose: Allografts have been shown useful in the reconstruction of bone defects after tumor resection. This study aimed to investigate the feasibility of using massive allografts to reconstruct bone defects after resection of extremity osteosarcomas. Methods: The clinical data of 15 patients treated with massive allograft reconstruction after resection of extremity osteosarcomas from January 2005 to January 2008 were retrospectively reviewed. Neoadjuvant and postoperative chemotherapy was used in all patients. The postoperative functions of the salvaged limbs were evaluated using the scoring system proposed by the Musculoskeletal Tumor Society (MSTS). Results: All patients were followed up for a mean of 61 months (range, 14–99 months). No nonunion occurred during follow-up. The mean time to union was 9 months (range, 3–21 months). No immune rejection, allograft infection, allograft fracture, and limb length disparity occurred. However, 2 patients had broken implants. The mean MSTS score at the last follow-up was 26 points. Four patients died and 2 patients had tumor recurrence. The 5-year disease free survival rate was 73.3%. Conclusion: Massive allograft reconstruction is safe and effective for bone defects caused by resection of extremity osteosarcomas. Highlights: We reviewed the clinical data of 15 patients. Neoadjuvant and postoperative chemotherapy was used in all patients. All patients were followed up for a mean of 61 months (range, 14–99 months). Bone union was evaluated using X-ray every 3 months.